Bioinformatics analysis of lncRNA-related ceRNA networks in the peripheral blood lymphocytes of Kazakh patients with essential hypertension in Xinjiang - Wang, Yan; Gao, Jie; Zhang, Liang; Yang, Rui; Zhang, Yingying; Shan, Liya; Li, Xinzhi; Ma, Ketao (Frontiers in Cardiovascular Medicine, 2023)
Objective Here, we aimed to investigate long non-coding RNA (lncRNA) expression characteristics in the peripheral blood lymphocytes of Xinjiang Kazakh people with essential hypertension and the underlying regulatory mechanisms of competing endogenous RNAs (ceRNA). Methods From April 2016 to May 2019, six Kazakh patients with essential hypertension and six Kazakh healthy participants were randomly selected from the inpatient and outpatient cardiology departments of the First Affiliated Hospital of Shihezi University Medical College, Xinjiang. After detecting the expression levels of lncRNA and mRNA in the peripheral blood lymphocytes using gene chip technology, their levels in the hypertensive group were compared with those in the control group. Six differentially expressed lncRNAs were randomly selected for real-time PCR to verify the accuracy and reliability of the gene chip results. GO functional clustering and KEGG pathway analyses were performed for differentially expressed genes. The ceRNA regulatory network of lncRNA-miRNA-mRNA was constructed, followed by visualization of the results. The expressions of miR-139-5p and DCBLD2 after PVT1 overexpression in 293T cells were detected by qRT-PCR and Western blot. Results In the test group, 396 and 511 differentially expressed lncRNAs and mRNAs, respectively, were screened out. The trend of real-time PCR results was consistent with that of the microarray results. The differentially expressed mRNAs were found to be primarily involved in the adhesion spot, leukocyte migration via endothelial cells, gap junction, actin cytoskeleton regulation, and extracellular matrix-receptor interaction signaling pathways. By constructing the ceRNA regulatory network, we found that lncRNA PVT1-miR-139-5p-DCBLD2 has a potential ceRNA regulatory mechanism involved in the development of essential hypertension in Xinjiang Kazakh people. In 293T cells, lncRNA PVT1 overexpression inhibited miR-139-5p and DCBLD2 levels. Conclusions Our findings indicate that differentially expressed lncRNAs may be involved in the development of essential hypertension. lncRNA PVT1-miR-139-5p-DCBLD2 was indicated to comprise a potential ceRNA regulatory mechanism involved in the development of essential hypertension in the Xinjiang Kazakh population. Thus, it may act as a novel screening marker or therapeutic target for essential hypertension in this population.